A hollow carbon dot@molybdenum carbide nanoreactor and its preparation method and catalytic hydrogen production application

By growing carbon spots on the surface of the hollow Mo2C nanoreactor, forming a hollow CD@Mo2C nanoreactor, the problems of insufficient hydrogen desorption activity and poor stability in alkaline electrolysis are solved, and efficient catalytic water cracking is achieved in alkaline environments, providing a low-cost and high-performance catalytic system.

CN117779098BActive Publication Date: 2025-04-15ANHUI AGRICULTURAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311835357.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-04-15
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

In the prior art, when transition metal carbides such as Mo2C are used as electrocatalysts in alkaline electrolysis, hydrogen desorption activity is insufficient and stability is poor, making it difficult to effectively catalyze water cracking in an alkaline environment.

Method used

By growing carbon dots in situ on the surface of the hollow Mo2C nanoreactor, a hollow CD@Mo2C nanoreactor is formed, and prepared by solvothermal method to adjust the strength of the Mo-H bond and improve catalytic activity and stability.

Benefits of technology

The hollow CD@Mo2C nanoreactor significantly improves the electrocatalytic hydrogen production activity in alkaline electrolytes, enhances the mechanical stability and electrochemical activity of the catalyst, and provides a low-cost and high-performance catalytic system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117779098B_ABST
    Figure CN117779098B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of energy electrocatalysis, and in particular refers to a hollow carbon dot @ molybdenum carbide nanoreactor, a preparation method thereof, and a catalytic hydrogen production application. The hollow carbon dot @ molybdenum carbide nanoreactor is a uniformly monodispersed three-dimensional nanosphere with a hollow structure inside, wherein a hollow molybdenum carbide (Mo2C) nanoreactor is used as a carrier, and carbon dots (CD) are in situ grown on the surface of the hollow Mo2C nanoreactor. The hollow CD@Mo2C nanoreactor electrocatalytic materials with different carbon contents prepared by the present invention exhibit different electrocatalytic hydrogen production activities in alkaline electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy electrocatalysis, and in particular refers to a hollow carbon dot@molybdenum carbide nanoreactor, a preparation method thereof, and an application of catalytic hydrogen production. Background Art

[0002] With the extensive use of fossil fuels, environmental and energy issues are becoming increasingly prominent. Therefore, vigorously developing renewable energy is an inevitable trend in today's research. Hydrogen energy, as a new type of clean and renewable energy with a large calorific value, has received widespread attention. Electrocatalytic water splitting is considered by researchers and entrepreneurs to be the most promising and ideal hydrogen production technology. To date, precious metal-based materials (such as Pt, Ir, and Ru-based catalysts) have been widely studied for hydrogen production. Unfortunately, scarcity and high prices limit their widespread application. Therefore, the development of low-cost, high-performance precious metal-free catalysts is one of the key tasks.

[0003] Transition metal carbides (TMC) such as molybdenum carbide (Mo 2 C) has an electronic structure similar to that of Pt and has great application prospects as a non-precious metal electrocatalyst in electrochemical energy conversion reactions. 2 The high density of d-orbital vacancies in C leads to a strong Mo-H bond, which makes hydrogen from Mo 2 Therefore, compared with noble metal-based hydrogen evolution reaction (HER) catalysts, Mo 2 The performance of C catalysts is still insufficient. Therefore, researchers have explored the use of transition metal modifiers to adjust the strength of Mo-H bonds, which can significantly improve the HER performance. However, during the electrocatalytic process, metal dopants may dissolve in the electrolyte, resulting in poor stability. Non-metallic carbon dots such as Mo 2 C not only promotes the desorption of H* but also improves its stability.

[0004] Non-precious metal-based catalysts have very low proton activity in alkaline solutions, and the slow water dissociation step in alkaline electrolysis greatly reduces the catalytic activity of alkaline hydrogen evolution reaction catalysts. The HER kinetics in alkaline electrolytes are much slower than those in acidic electrolytes. Therefore, the development of efficient catalysts is crucial. Conventional alkaline electrolysis uses high-surface-area Ni or Ni alloys, which unfortunately tend to form hydrides and even become brittle, leading to disintegration. Studies have shown that Mo x C yIt has excellent water dissociation ability and thus has the potential to be an alkaline HER electrocatalyst. In a stable electrochemical process, the hierarchical hollow nanostructure assembled from two-dimensional nanosheets has great advantages in the mechanical stability of the catalyst. The hollow structure can effectively promote the contact between the electrode and the electrolyte, enhance the mass transfer of the electrolyte, and quickly transport it to the catalytic surface, thereby improving the electrocatalytic activity. Mo sites are Mo 2 The active site of C HER. 2 The carbon deposition reaction during the carbon addition process will cover the Mo catalytic sites, resulting in poor HER activity. Therefore, how to expose more Mo catalytic sites is the key to improving Mo 2 C is an important factor for hydrogen evolution activity. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a hollow CD@Mo 2 C nanoreactor, its preparation method and application in catalytic hydrogen production.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A hollow carbon dot@molybdenum carbide nanoreactor, comprising a hollow Mo as a carrier 2 C nanoreactor, and in situ growth in the hollow Mo 2 Carbon dots (CDs) on the surface of C nanoreactor, the CD@Mo 2 The C nanoreactor is a uniform, monodispersed three-dimensional nanosphere with a hollow structure inside.

[0008] A method for preparing a hollow carbon dot@molybdenum carbide nanoreactor comprises the following steps:

[0009] (1) preparing an aqueous solution of a molybdenum salt, and adding glucose to the aqueous solution of the molybdenum salt at room temperature to adjust the viscosity of the solution to obtain solution I;

[0010] (2) preparing an oil phase solution of a cationic surfactant (CSAA): dispersing the cationic surfactant into two oil phase alcohols with different carbon chain lengths at room temperature to control the morphology of the surfactant, thereby obtaining solution II;

[0011] (3) Adding the solution I of step (1) dropwise into the solution II of step (2), controlling the reversal of the micelles, the micelle morphology changes from oil-in-water type to critical type and finally to water-in-oil type; then adding hydrochloric acid and thiourea, and undergoing a solvothermal reaction, a monodisperse MoS 2 / CSAA precursor;

[0012] (4) The monodisperse MoS 2 / CSAA precursor is heat treated to obtain monodispersed hollow MoS 2 Nanospheres;

[0013] (5) The monodispersed hollow MoS 2 The nanospheres are then carbonized to obtain hollow Mo 2 C nanoreactor;

[0014] (6) The monodispersed hollow Mo in step (5) 2 C nanoreactor was then heat treated to obtain hollow CD@Mo with different carbon contents. 2 C nanoreactor.

[0015] Furthermore, the molybdenum salt in step (1) is sodium molybdate, and the molar ratio of glucose to the molybdenum salt is 5:1.

[0016] Furthermore, in step (2), the cationic surfactant is hexadecyltrimethylammonium bromide, the oil phase alcohol is n-butanol and ethylene glycol, and the volume ratio of n-butanol to another oil phase alcohol is 1:0.5.

[0017] Furthermore, in step (3), the volume ratio of solution I to solution II is 2:1; the volume ratio of the hydrochloric acid to the water in solution I is 1:300; the molar ratio of the amount of thiourea added to the amount of molybdenum salt is 30:1; and the solvent thermal reaction conditions in step (3) are 200° C. for 24 hours.

[0018] Furthermore, in the step (4), the monodisperse MoS 2 The heat treatment operation of the / CSAA precursor is as follows: heat treatment at 900°C for 3h in a tube furnace under argon atmosphere, with a heating rate of 5°C / min.

[0019] Furthermore, in step (5), monodispersed hollow MoS 2 The carbonization process of the nanospheres is as follows: 2 The reaction conditions for heat treatment of nanospheres in a methane / hydrogen atmosphere are: 800°C for 3 h, with a heating rate of 5°C / min.

[0020] Furthermore, the reaction conditions of the heat treatment in step (6) are as follows: heat treatment at 700, 750, 800, 850, 900°C in an argon gas-enclosed tube furnace for 1-5h, with a heating rate of 1-5°C / min. The obtained samples are named CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 C-5, preferred

[0021] Furthermore, the heat treatment conditions in step (6) are 800° C. for 3 h, with a heating rate of 5° C. / min.

[0022] The third object of the present invention is to provide an application of the hollow carbon dot@molybdenum carbide nanoreactor as an electrocatalytic material for electrocatalytic hydrogen production in an alkaline electrolyte.

[0023] Technical effects of the present invention:

[0024] (1) Hollow CD@Mo with different carbon contents prepared by the present invention 2 The C nanoreactor electrocatalytic materials exhibit different electrocatalytic hydrogen production activities in alkaline electrolytes, providing a new idea for solving energy shortages and preparing green hydrogen.

[0025] (2) The preparation method provided by the present invention has a simple process, abundant and low-cost raw materials, and has realistic application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 for CD@Mo 2 Schematic diagram of the process for preparing C nanoreactor.

[0027] Figure 2 is MoS in Example 1 2 Field emission scanning electron microscopy (FESEM) images;

[0028] Figure 2 When a is 10 μm, MoS 2 Field emission scanning electron microscopy (FESEM) images of nanospheres;

[0029] Figure 2 b is 1 μm when MoS 2 Field emission scanning electron microscopy (FESEM) images of nanospheres;

[0030] Figure 2 When c is 200nm, MoS 2 Field emission scanning electron microscopy (FESEM) images of nanospheres;

[0031] Figure 2 MoS when d is 100nm 2 Field emission scanning electron microscopy (FESEM) images of nanospheres.

[0032] Figure 3 is MoS in Example 1 2 Transmission electron microscopy (TEM) images of

[0033] Figure 3 When a is 1 μm, MoS2 Transmission electron microscopy (TEM) images of nanospheres;

[0034] Figure 3 When b is 500nm, MoS 2 Transmission electron microscopy (TEM) images of nanospheres;

[0035] Figure 3 When c is 500nm, MoS 2 Transmission electron microscopy (TEM) images of nanospheres;

[0036] Figure 3 MoS when d is 200nm 2 Transmission electron microscopy (TEM) image of the nanospheres.

[0037] Figure 4 CD@Mo in Example 1 2 C-1, CD@Mo 2 C-2、CD@Mo2C-3、CD@Mo 2 C-4 and CD@Mo 2 Field emission scanning electron microscopy (FESEM) image of the C-5 nanoreactor;

[0038] Figure 4 CD@Mo when a is 10μm, 500nm and 200nm 2 Field emission scanning electron microscopy (FESEM) image of the C-1 nanoreactor;

[0039] Figure 4 CD@Mo when b is 10μm, 500nm and 200nm 2 Field emission scanning electron microscopy (FESEM) image of the C-2 nanoreactor;

[0040] Figure 4 CD@Mo when c is 10μm, 500nm and 200nm 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor;

[0041] Figure 4 CD@Mo when d is 10μm, 500nm and 200nm 2 Field emission scanning electron microscopy (FESEM) image of the C-4 nanoreactor;

[0042] Figure 4 CD@Mo when e is 10μm, 500nm and 200nm 2 Field emission scanning electron microscopy (FESEM) image of the C-5 nanoreactor.

[0043] Figure 5CD@Mo in Example 1 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Transmission electron microscopy (TEM) image of the C-5 nanoreactor;

[0044] Figure 5 CD@Mo when a is 1μm, 200nm and 100nm 2 Transmission electron microscopy (TEM) image of C-1 nanoreactor;

[0045] Figure 5 b CD@Mo at 1μm, 200nm and 100nm 2 Transmission electron microscopy (TEM) image of the C-2 nanoreactor;

[0046] Figure 5 CD@Mo when c is 1μm, 200nm and 100nm 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor;

[0047] Figure 5 CD@Mo when d is 1μm, 200nm and 100nm 2 Transmission electron microscopy (TEM) image of the C-4 nanoreactor;

[0048] Figure 5 CD@Mo when e is 1μm, 200nm and 100nm 2 Transmission electron microscopy (TEM) image of the C-5 nanoreactor.

[0049] Figure 6 CD@Mo in Example 1 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor;

[0050] Figure 6 CD@Mo when a is 5μm 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor;

[0051] Figure 6 CD@Mo when b is 200nm 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor;

[0052] Figure 6 CD@Mo when c is 100nm 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor.

[0053] Figure 7 CD@Mo in Example 1 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor;

[0054] Figure 7 When a is 1 μm, CD@Mo 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor;

[0055] Figure 7 CD@Mo when b is 200nm 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor;

[0056] Figure 7 When c is 5nm, CD@Mo 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor.

[0057] Figure 8 CD@Mo in Example 1 2 Elemental mapping of the C-3 nanoreactor;

[0058] Figure 8 CD@Mo when a is 200 nm 2 Field emission scanning electron microscopy (FESEM) images corresponding to the elemental mapping of the C-3 nanoreactor;

[0059] Figure 8 CD@Mo when b is 200nm 2 Mo elemental mapping of C-3 nanoreactor;

[0060] Figure 8 CD@Mo when c is 200nm 2 C element mapping of the C-3 nanoreactor.

[0061] Fig. 9 CD@Mo in Example 1 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 C-5 nanoreactor structure characterization diagram;

[0062] Fig. 9 a is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2X-ray diffraction (XRD) pattern of C-5 nanoreactor;

[0063] Fig. 9 b is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Raman image of C-5 nanoreactor;

[0064] Fig. 9 c is CD@Mo 2 C-3 and CD@Mo 2 X-ray photoelectron spectroscopy (XPS) of the C-5 nanoreactor;

[0065] Fig. 9 d is the Fourier transform infrared (FTIR) spectrum of CD@Mo2C-1, CD@Mo2C-2, CD@Mo2C-3, CD@Mo2C-4 and CD@Mo2C-5 nanoreactors.

[0066] Fig.10 for CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Hydrogen production performance of C-5 nanoreactor in alkaline electrolyte;

[0067] Fig.10 a is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 LSV diagram of C-5;

[0068] Fig.10 b is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Parabolic fitting diagram of the overpotential of the C-5 nanoreactor;

[0069] Fig.10 c is CD@Mo 2 Current stability diagram of the C-3 nanoreactor.

[0070] Fig.11 CD@Mo in Example 2 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Hydrogen production performance of C-5 nanoreactor in alkaline electrolyte;

[0071] Fig.11 a is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Tafel slope plot of C-5 nanoreactor;

[0072] Fig.11 b is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 EIS graph of C-5 nanoreactor;

[0073] Fig.11 c is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Double layer capacitance diagram of C-5 nanoreactor;

[0074] Fig.11 d is CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Comparison of active surface areas of C-5 nanoreactors.

[0075] Fig.12 CD@Mo in Example 2 2 In situ characterization and post-cycling testing of C-3;

[0076] Fig.12 a is CD@Mo 2 In situ XRD pattern of C-3 nanoreactor;

[0077] Fig.12 b is CD@Mo2 In situ Raman image of C-3 nanoreactor;

[0078] Fig.12 c is CD@Mo 2 XPS graph of C-3 nanoreactor after electrocatalytic test;

[0079] Fig.12 d is CD@Mo 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor after electrocatalytic testing.

[0080] Fig.13 CD@Mo in Example 2 2 Field emission scanning electron microscope (FESEM) image of C-3 after electrochemical testing;

[0081] Fig.13 When a is 10 μm, CD@Mo 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor;

[0082] Fig.13 CD@Mo when b is 1μm 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor;

[0083] Fig.13 CD@Mo when c is 200nm 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor;

[0084] Fig.13 CD@Mo when d is 100nm 2 Field emission scanning electron microscopy (FESEM) image of the C-3 nanoreactor.

[0085] Fig.14 CD@Mo in Example 2 2 Transmission electron microscopy (TEM) image of C-3 after electrochemical testing;

[0086] Fig.14 When a is 1 μm, CD@Mo 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor;

[0087] Fig.14 CD@Mo when b is 500nm 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor;

[0088] Fig.14 CD@Mo when c is 200nm 2Transmission electron microscopy (TEM) image of the C-3 nanoreactor;

[0089] Fig.14 CD@Mo when d is 100nm 2 Transmission electron microscopy (TEM) image of the C-3 nanoreactor.

[0090] Fig.15 This is the theoretical calculation diagram in the example;

[0091] Fig.15 a is CD@Mo 2 C and Mo 2 C Nanoreactor state density (pDOS) diagram;

[0092] Fig.15 b is CD@Mo 2 C and Mo 2 C Gibbs free energy diagram of the nanoreactor;

[0093] Fig.15 c is CD@Mo 2 C Nanoreactor differential charge density (EDD) diagram;

[0094] Fig.15 d is CD@Mo 2 Chemical model and reaction mechanism diagram of C nanoreactor. DETAILED DESCRIPTION

[0095] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0096] Example 1

[0097] Hollow CD@Mo was prepared by a typical solvothermal method. 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-、CD@Mo 2 C-4 and CD@Mo 2 C-5 nanoreactor.

[0098] 1 mmol of sodium molybdate was dissolved in 300 mL of deionized water, and then 5 mmol of glucose was added to obtain an aqueous solution; 100 mL of n-butanol and 50 mL of ethylene glycol were mixed evenly, and then 15 mmol of hexadecyltrimethylammonium bromide was added to obtain an oil solution; the aqueous solution was added dropwise to the oil solution, and after stirring for 2 h, 1 mL of hydrochloric acid and 30 mmol of thiourea were added in sequence, and after stirring for 3 h, a solvothermal reaction was performed; the reaction was continued at 200 ° C for 24 h; after centrifugation and washing, a monodispersed MoS 2 / CSAA precursor; heat treatment of the precursor, specifically: heat treatment at 900 ° C for 3 h in a tube furnace under argon atmosphere, with a heating rate of 5 ° C / min, to obtain hollow MoS 2 Nanospheres. Hollow MoS 2 The nanospheres were heat treated in a methane / hydrogen atmosphere at 800°C for 3 h with a heating rate of 5°C / min to obtain hollow Mo 2 C nanoreactor. Finally, the hollow Mo 2 The C nanoreactor was heat treated in an argon gas-enclosed tube furnace at 700, 750, 800, 850, and 900 °C for 3 h at a heating rate of 5 °C / min. The obtained samples were named CD@Mo 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 C-5. The CD@Mo 2 The schematic diagram of the preparation process of C nanoreactor is shown in Figure 1 shown.

[0099] CD@Mo 2 Characterization of C Nanoreactor:

[0100] (1) MoS prepared in Example 1 2 Field emission scanning electron microscopy was performed, and the specific results are as follows Figure 2 As shown, the prepared MoS 2 Three-dimensional nanospheres assembled from two-dimensional sheets.

[0101] (2) MoS prepared in Example 1 2 Transmission electron microscopy characterization was performed, and the specific results are as follows Figure 3 As shown, the prepared MoS 2 Nanospheres are hollow structures.

[0102] (3) In order to change the carbon content, hollow Mo was subjected to 2 C nanoreactor was annealed. SEM and TEM were used to study the Mo 2C The morphology and structure of the nanoreactor.

[0103] Figure 4 CD@Mo prepared in Example 1 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 Field emission scanning electron microscopy characterization of the C-5 nanoreactor shows that the prepared CD@Mo 2 C nanoreactors are uniformly monodispersed three-dimensional nanospheres. Figure 5 CD@Mo prepared in Example 1 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 C-5 nanoreactor was characterized by transmission electron microscopy. Figure 5 The prepared CD@Mo 2 C nanoreactor is a hollow structure, i.e. CD@Mo 2 The C nanoreactor exhibits a uniform monodisperse hollow structure after annealing. As the annealing temperature increases, the carbon particles on the surface of the nanoreactor gradually decrease.

[0104] (4) CD@Mo prepared in Example 1 2 The C-3 nanoreactor was characterized by field emission scanning electron microscopy and transmission electron microscopy. The specific results are as follows Figure 6-7 As shown, Figure 6-7 The FESEM and TEM images showed that the high-resolution transmission electron microscopy (HRTEM) images showed a lattice spacing of 0.24 nm, corresponding to Mo 2 C (002) crystal plane. In addition, in the two-dimensional Mo 2 Carbon dots can be clearly observed on the C nanosheets. 2 The C-3 nanoreactor was characterized by elemental mapping. The specific results are as follows Figure 8 As shown, it shows that Mo and C are uniformly distributed in the hollow CD@Mo 2 C-3 nanoreactor.

[0105] (5) CD@Mo in Example 1 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2The C-5 nanoreactor was subjected to structural characterization, including X-ray diffraction (XRD), Raman, X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR).

[0106] Through X-ray diffraction (XRD) pattern ( Fig. 9 a) It can be seen that CD@Mo 2 The XRD peaks of C at 34.1°, 37.3°, 38.9°, 61.3°, and 74.3° correspond to hexagonal Mo 2 The (100), (002), (101), (110) and (112) crystal planes of C, among which the peak at 20.6° is attributed to carbon dots. By comparison, it can be seen that with the increase of annealing temperature, the carbon peak gradually decreases.

[0107] In the Raman spectrum ( Fig. 9 b), 814.7 and 990.2 cm −1 The peak corresponds to Mo 2 Characteristic vibrations of C. 1353.7 and 1587.4 cm −1 The characteristic peaks belong to the D and G bands of carbon materials. By comparison, it can be seen that the intensity of the characteristic peaks of the D and G bands decreases with the increase of annealing temperature. It is worth noting that at 900°C, the characteristic peaks of carbon disappear, indicating that there are no carbon dots in the prepared catalyst, which is consistent with the XRD results.

[0108] X-ray photoelectron spectroscopy (XPS) reveals that CD@Mo 2 C-3 and CD@Mo 2 Chemical state and electronic structure of C-5 ( Fig. 9 c) The XPS spectrum of Mo 3d can be fitted into six peaks, corresponding to Mo 2+ , Mo 4+ and Mo 6+ The peaks at 228.8 and 231.9 eV correspond to Mo 2+ , this is Mo 2 Typical characteristics of C. and CD@Mo 2 Compared to C-5, CD@Mo 2 Mo in C-3 2+ The peak shifted by 0.12 eV to a higher binding energy, indicating that the introduction of carbon dots donated electrons to Mo. The peaks observed at 229.7 and 233.5 eV correspond to the Mo 4+ , the peaks at 232.8 and 236.0 eV correspond to Mo 6+ The two peaks correspond to the Mo species oxidized during the preparation process. FTIR shows that different carbon contents have an effect on the Mo 2 C has no effect ( Fig. 9 d).

[0109] Example 2

[0110] CD@Mo prepared in Example 1 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 The C-5 nanoreactor was used for electrochemical experiments. The specific operation is as follows:

[0111] CD@Mo 2 The C nanoreactor electrocatalytic material was used as the working electrode, and all electrochemical tests were performed at room temperature using an electrochemical workstation. Ag / AgCl was used as the reference electrode, and a Pt wire electrode was used as the counter electrode. All polarization curves were measured in the range of 0.1 to -0.3 V (RHE) at 5 mV s −1 The potential was calibrated by a reversible hydrogen electrode (RHE). The Tafel curve was calculated based on η = a + blog (abs (j)) (b: Tafel slope, j: current density). The current density was calculated from 20 mV s −1 To 200 mV s −1 Closed cyclic voltammetry (CV) at different scan rates for the hollow CD@Mo 2 The double layer capacitance of the C nanoreactor catalyst was studied. All electrochemical impedance spectroscopy (EIS) curves were tested in 1mmol / L KOH electrolyte, and the initial potential was the open circuit potential. The high frequency was 10 6 Hz, and the low frequency is 0.01 Hz.

[0112] CD@Mo prepared in Example 1 2 C-1, CD@Mo 2 C-2, CD@Mo 2 C-3, CD@Mo 2 C-4 and CD@Mo 2 The hydrogen production performance of C-5 nanoreactor in alkaline electrolyte is shown in Fig.10 As shown, from Fig.10 As can be seen in a, the prepared CD@Mo 2 The C-3 catalyst exhibited superior HER catalytic performance at 10 mA cm −2 The overpotential at annealing temperature is 57 mV. The relationship between the overpotential and the annealing temperature shows that the appropriate carbon content can significantly improve the HER performance ( Fig.10 b). In addition, to evaluate the CD@Mo 2The stability of C-3 was tested by electrolysis using a current-time curve. After 120 hours of testing at -1.123V, CD@Mo 2 C-3 exhibits excellent HER durability ( Fig.10 c).

[0113] To evaluate the CD@Mo 2 The HER kinetics of C and the Tafel slope were measured and calculated. 2 C-3 exhibited the lowest Tafel slope of 96 mV dec. -1 ( Fig.11 a). Electrochemical impedance spectroscopy (EIS) ( Fig.11 b) The kinetic behavior of the electrodes was also studied. All EIS curves were semicircular, which was consistent with the charge transfer resistance (R ct ). Compared with other catalysts, CD@Mo 2 C-3 showed the lowest R ct , indicating that it has the fastest charge transfer kinetics. In addition, the double layer capacitance (C dl ) to further compare the electrochemically active surface area (ECSA) of the prepared catalysts. The capacitance current changes with the scan rate. Fig.11 As shown in c, it can be observed that CD@Mo 2 C-3 showed a larger C dl , indicating that it exposes more catalytic active sites and exhibits stronger catalytic activity than other catalysts. Normalization is performed by a more intuitive comparison of the number of catalytic active areas. Fig.11 As shown in d, compared with other prepared catalysts, CD@Mo 2 C-3 has the most effective active surface area.

[0114] CD@Mo 2 The stability of C-3 during electrocatalysis in 1.0 M KOH electrolyte was investigated by in situ XRD ( Fig.12 a). Mo 2 The peak of C remains unchanged without any new peaks appearing. These results indicate that CD@Mo 2 C-3 has excellent durability. CD@Mo was studied by in situ Raman spectroscopy. 2 The structural evolution of the C-3 electrode under different voltages. Before the voltage is applied, the Mo 2 The vibration peaks of C are at 814.7 and 990.2 cm −1 The in situ Raman data were obtained in the catalytic experiment. A two-dimensional mapping image was generated based on the Raman spectra at different voltages ( Fig.12 b). Mo 2 The vibration peak position of C remained unchanged, and no new characteristic peaks appeared during the constant electrocatalytic process, indicating that the composition of the nanoreactor was stable during the catalytic process. 2 The surface chemical state of C-3 after electrocatalytic reaction was further studied by XPS and TEM. Mo 3d can be observed in the XPS spectrum. 2+ 、Mo 4+ and Mo 6+ ( Fig.12 c). The results show that CD@Mo 2 The chemical state of C-3 remains unchanged during the electrochemical process. TEM images after electrocatalytic reaction show that CD@Mo 2 The hollow structure of C-3 remains unchanged, further confirming that CD@Mo 2 The stability of the C-3 structure ( Fig.12 d). In the HER process, CD@Mo 2 The characterization results of the structure and composition of C-3 demonstrated its stability.

[0115] CD@Mo after electrochemical testing in Example 2 2 C-3 was characterized by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM), see Figure 13-14 , indicating that the CD@Mo 2 The C-3 nanoreactor still has a uniform three-dimensional spherical structure and no changes occurred during the electrochemical test.

[0116] Catalytic mechanism studies

[0117] Density functional theory (DFT) calculations were used to investigate the effect of surface carbon dots on the HER activity in alkaline electrolytes. The d-band center revealed the interaction between the adsorbate and the metal, and the CD@Mo 2 The improvement mechanism of C. The density of states (pDOS) reveals that in CD@Mo 2 The orbital hybridization between Mo 3d orbital and C 2p orbital in C indicates that the Mo site is effectively optimized. 2 C and Mo 2 The d-band centers of active Mo atoms on the C surface are -0.21 and -0.19 eV respectively. Fig.15 a). The calculation results show that the carbon dots reduce the antibonding energy, causing the d-band center to deviate from the Fermi level, thereby weakening the interaction between the adsorbed species and the Mo site, and ultimately accelerating the HER kinetics. The calculated adsorption and dissociation free energies ( Fig.15 b) Display, CD@Mo 2The water adsorption barrier (step 1) of C is -0.98 eV, while that of Mo 2 The water adsorption barrier of C is 0.36 eV, indicating that CD@Mo 2 C has excellent adsorption and desorption capacity for water. 2 Dissociation of H 2 O molecules require a barrier of 0.7 eV, while Mo 2 C requires a barrier of -1.85 eV. The lowest barrier in step 2 represents CD@Mo 2 The fastest dissociation kinetics of H* absorbed on C. This also indicates that CD@Mo 2 Carbon dots on C nanosheets promote the CD@Mo 2 These results can also explain why CD@Mo 2 C exhibits better HER performance. The charge distribution of Mo and C atoms was investigated by calculating the electron density difference (EDD). Fig.15 c) In situ generated carbon dots facilitate electron transfer to Mo sites and water dissociation. The HER mechanism in alkaline electrolytes suggests that this process involves the adsorption and dissociation of water molecules, such as Fig.15 As shown in d, it is CD@Mo 2 Chemical adsorption model and process of C. In summary, the DFT results show that Mo 2 The carbon dots on C nanosheets can enhance the desorption of H* and improve the performance of HER in alkaline electrolytes.

[0118] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a hollow carbon dot@molybdenum carbide nanoreactor, characterized in that: The hollow carbon dot@molybdenum carbide nanoreactor is a uniformly monodispersed three-dimensional nanosphere with a hollow structure inside, wherein the hollow Mo2C nanoreactor is used as a carrier, and carbon dots CD are in-situ grown on the surface of the hollow Mo2C nanoreactor; The preparation method comprises the following steps: (1) preparing an aqueous solution of a molybdenum salt, and adding glucose to the aqueous solution of the molybdenum salt at room temperature to adjust the viscosity of the solution to obtain solution I; (2) preparing an oil phase solution of a cationic surfactant CSAA: dispersing the cationic surfactant CSAA into two oil phase alcohols with different carbon chain lengths at room temperature to control the morphology of the surfactant, thereby obtaining solution II; (3) adding the solution I of step (1) dropwise into the solution II of step (2) to control the reversal of the micelles, so that the micelle morphology changes from oil-in-water type to critical type and finally to water-in-oil type; then adding hydrochloric acid and thiourea to obtain a monodisperse MoS2 / CSAA precursor through a solvothermal reaction; (4) heat treating the monodisperse MoS2 / CSAA precursor of step (3) to obtain monodisperse hollow MoS2 nanospheres; (5) The monodispersed hollow MoS2 nanospheres in step (4) are further carbonized to obtain a hollow Mo2C nanoreactor; (6) heat-treating the monodispersed hollow Mo2C nanoreactor in step (5) to obtain hollow CD@Mo2C nanoreactors with different carbon contents; The operation of step (4) is as follows: heat treatment at 900°C for 3h in an argon atmosphere tube furnace with a heating rate of 5°C / min; The operation of step (5) is as follows: the hollow MoS2 nanospheres are heat treated in a methane / hydrogen atmosphere under the following reaction conditions: heat treatment at 800°C for 3h, with a heating rate of 5°C / min.

2. The method for preparing the hollow carbon dot@molybdenum carbide nanoreactor according to claim 1, characterized in that: The molybdenum salt in step (1) is sodium molybdate, and the molar ratio of glucose to the molybdenum salt is 5:

1.

3. The method for preparing the hollow carbon dot@molybdenum carbide nanoreactor according to claim 1, characterized in that: In the step (2), the cationic surfactant is hexadecyltrimethylammonium bromide, the oil phase alcohol is n-butanol and ethylene glycol, and the volume ratio of n-butanol to ethylene glycol is 1:0.

5.

4. The method for preparing the hollow carbon dot@molybdenum carbide nanoreactor according to claim 1, characterized in that: The volume ratio of solution I to solution II in step (3) is 2:1; the volume ratio of hydrochloric acid to water in solution I is 1:300; the molar ratio of the amount of thiourea added to the amount of molybdenum salt is 30:1; the conditions for the solvent thermal reaction in step (3) are 200° C. for 24 hours.

5. The method for preparing the hollow carbon dot@molybdenum carbide nanoreactor according to claim 1, characterized in that: The reaction conditions of the heat treatment in step (6) are as follows: heat treatment at 700, 750, 800, 850, 900°C in an argon atmosphere tube furnace for 1-5h, and a heating rate of 1-5°C / min. The obtained samples are named CD@Mo2C-1, CD@Mo2C-2, CD@Mo2C-3, CD@Mo2C-4 and CD@Mo2C-5, respectively.

6. The method for preparing the hollow carbon dot@molybdenum carbide nanoreactor according to claim 1, characterized in that: The heat treatment conditions in step (6) are 800° C. for 3 h, and the heating rate is 5° C. / min.

7. An application of the hollow carbon dot@molybdenum carbide nanoreactor prepared by the preparation method according to any one of claims 1 to 6 as an electrocatalytic material for electrocatalytic hydrogen production in an alkaline electrolyte.

Citation Information

Patent Citations

  • Monodisperse, molecular carbon intercalation and body type MoS2 / C nanoreactor as well as synthesis method and application of monodisperse, molecular carbon intercalation and body type MoS2 / C nanoreactor

    CN114192168A